VD_FINDINFO Jug / 2021 / 271 vom 16. März 2021 - VD Tribunal cantonal (2021)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, RÉPRIMANDE, PROPORTIONNALITÉ | 14 LPers-VD, 16 LPers-VD, 50 LPers-VD, 59 LPers-VD, 124 RLPers-VD, 135 RLPers-VD, 139 RLPers-VD